Peripheral upregulation of Parkinson’s disease-associated genes encoding α-synuclein, β-glucocerebrosidase, and ceramide glucosyltransferase in major depression - Brazdiş, Răzvan-Marius; Zimmermann, Claudia von; Lenz, Bernd; Kornhuber, Johannes; Mühle, Christiane (International journal of molecular sciences, 2024)
Due to the high comorbidity of Parkinson’s disease (PD) with major depressive disorder (MDD) and the involvement of sphingolipids in both conditions, we investigated the peripheral expression levels of three primarily PD-associated genes: α-synuclein (SNCA), lysosomal enzyme β-glucocerebrosidase (GBA1), and UDP-glucose ceramide glucosyltransferase (UGCG) in a sex-balanced MDD cohort. Normalized gene expression was determined by quantitative PCR in patients suffering from MDD (unmedicated n = 63, medicated n = 66) and controls (remitted MDD n = 39, healthy subjects n = 61). We observed that expression levels of SNCA (p = 0.036), GBA1 (p = 0.014), and UGCG (p = 0.0002) were higher in currently depressed patients compared to controls and remitted patients, and expression of GBA1 and UGCG decreased in medicated patients during three weeks of therapy. Additionally, in subgroups, expression was positively correlated with the severity of depression and anxiety. Furthermore, we identified correlations between the gene expression levels and PD-related laboratory parameters. Our findings suggest that SNCA, GBA1, and UGCG analysis could be instrumental in the search for biomarkers of MDD and in understanding the overlapping pathological mechanisms underlying neuro-psychiatric diseases.